Acute Kidney Injury After Abdominal Surgery: Incidence, Risk Factors, and Outcome. (June 2016) - Long, Thorir E.; Helgason, Dadi; Helgadottir, Solveig; Palsson, Runolfur; Gudbjartsson, Tomas; Sigurdsson, Gisli H.; Indridason, Olafur S.; Sigurdsson, Martin I.
Abstract : BACKGROUND: Acute kidney injury (AKI) is a serious complication after major surgical procedures. We examined the incidence, risk factors, and mortality of patients who sustained AKI after abdominal surgery in a large population-based cohort. METHODS: All patients who underwent open and laparoscopic abdominal surgery (excluding genitourinary and abdominal vascular procedures), between 2007 and 2014 at the University Hospital in Reykjavik were identified and their perioperative serum creatinine (SCr) measurements used to identify AKI after surgery employing the Kidney Disease: Improving Global Outcome (KDIGO) criteria. Risk factors were evaluated using multivariate logistic regression analysis and 30-day mortality compared with a propensity score–matched control group. RESULTS: During the 8-year period, a total of 11, 552 abdominal surgeries were performed on 10, 022 patients. Both pre- and postoperative SCr measurements were available for 3902 (33.8%) of the surgical cases. Of these, 264 (6.8%) were complicated by AKI; 172 (4.4%), 49 (1.3%), and 43 (1.1%) were classified as KDIGO stages 1, 2 and 3, respectively. The overall incidence of AKI for patients with available SCr values was 67.7 (99% confidence interval [CI], 57.7–78.6) per 1000 surgeries. In logistic regression analysis, independent risk factors for AKI were female sex (odds ratio [OR] = 0.68; 99% CI, 0.47–0.98), hypertension (OR = 1.75; 99% CI, 1.10–2.74), preoperative chronic kidney disease (OR= 1.68; 99% CI, 1.12–2.50), ASA physical status classification of IV (OR = 9.48; 99% CI, 3.66–29.2) or V (OR = 21.4; 99% CI, 5.28–93.6), and reoperation (OR = 4.30; 99% CI, 2.36–7.70). Patients with AKI had greater 30-day mortality (18.2% vs 5.3%; P < 0.001) compared with propensity score–matched controls. CONCLUSIONS: AKI is an important complication of abdominal surgery. In addition to sex, hypertension, and chronic kidney disease, ASA physical status classification is an independent predictor of AKI. Individuals who develop AKI have substantially worse short-term outcomes, including higher 30-day mortality, even after correcting for multiple patient- and procedure-related risk factors. Abstract : Supplemental Digital Content is available in the text.